Racial and ethnic disparities in children and adults in the usage of continuous glucose monitors: a scoping review protocol - Forest Melton; D Jean McClelland; Linda Jepkoech Kimaru; Peter D Reaven; Kelly N.B. Palmer (BMJ Open)
Introduction This scoping review synthesises the existing literature on racial and ethnic disparities in the utilisation of continuous glucose monitors (CGMs) among adults and children with diabetes in the USA. The primary objective is to describe the extent and nature of these disparities, with the broader goal of informing future research and interventions to address health inequities.Methods and analysis Guided by the Joanna Briggs Institute methodological framework, this review will systematically search PubMed, Embase and Scopus for relevant studies. Included studies will focus on individuals diagnosed with type 1 or type 2 diabetes in the USA. Selection criteria will prioritise studies reporting demographic factors, CGM usage patterns and associated health outcomes. The primary outcome is the extent of racial and ethnic disparities in CGM utilisation. Data synthesis will use the National Institute on Minority Health and Health Disparities Framework (NIMHD) to uncover patterns of CGM utilisation among racial–ethnic groups. The NIMHD facilitates a multilevel examination of the factors influencing CGM initiation, continued use and attrition by integrating individual, interpersonal, community and societal level influences. This comprehensive approach provides a nuanced understanding of the barriers and facilitators shaping CGM usage across diverse populations. By applying the NIMHD framework, this review aims to identify existing disparities, uncover gaps in the literature and offer direction for future research and interventions.Ethics and dissemination As this study involves a review of previously published literature and does not involve human subjects research, institutional review board approval will not be pursued. Findings will be disseminated through peer-reviewed publications, conference presentations and lay summaries.Literature review registration number https://doi.org/10.17605/OSF.IO/RGW6M.